1996
DOI: 10.1182/blood.v88.1.236.236
|View full text |Cite
|
Sign up to set email alerts
|

T cells from patients with Hodgkin's disease have a defective T-cell receptor zeta chain expression that is reversible by T-cell stimulation with CD3 and CD28

Abstract: To investigate the mechanisms underlying the deficiency of T lymphocytes from patients with Hodgkin's disease, we investigated the expression of the T-cell receptor (TCR) zeta chain in patients with Hodgkin's disease. By flow cytometry using an anti-zeta chain monoclonal antibody, peripheral blood T lymphocytes from patients with untreated Hodgkin's disease were shown to express decreased levels of the TCR zeta chain. After stimulation by combined CD3 and CD28 cross- linking, T cells from Hodgkin's disease pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…Not all T lymphocytes isolated from the tumour environment or from the PB of patients with cancer are dysfunctional, and restoration of proliferative and cytolytic functions have been reported to occur in the presence of cytokines, such as interleukin (IL)‐2 (Whiteside, 1994; Tartour et al , 1995; Rabinowich et al , 1996a), IL‐7 or IL‐12 (Whiteside, 1999) or when the T cells are cross‐linked with anti‐CD3. For example, PB T lymphocytes from patients with untreated Hodgkin's disease show decreased levels of TCR zeta chain which, after combined CD3 and CD28 cross‐linking in vitro , upregulate their zeta chain protein expression to normal levels within 48 h (Renner et al , 1996). Only limited data are available for the in vivo effects of IL‐2 on expression of the zeta chain in T cells obtained from patients with cancer.…”
mentioning
confidence: 99%
“…Not all T lymphocytes isolated from the tumour environment or from the PB of patients with cancer are dysfunctional, and restoration of proliferative and cytolytic functions have been reported to occur in the presence of cytokines, such as interleukin (IL)‐2 (Whiteside, 1994; Tartour et al , 1995; Rabinowich et al , 1996a), IL‐7 or IL‐12 (Whiteside, 1999) or when the T cells are cross‐linked with anti‐CD3. For example, PB T lymphocytes from patients with untreated Hodgkin's disease show decreased levels of TCR zeta chain which, after combined CD3 and CD28 cross‐linking in vitro , upregulate their zeta chain protein expression to normal levels within 48 h (Renner et al , 1996). Only limited data are available for the in vivo effects of IL‐2 on expression of the zeta chain in T cells obtained from patients with cancer.…”
mentioning
confidence: 99%
“…These results, together with the evidence that effective LAK cells may be generated from leukaemic patients in disease remission (Lauria et al, 1994), are in contrast to the defective killing capacity of LAK effectors generated from AML patients at diagnosis (Foa et al, 1991a). T and cytotoxic cells in®ltrating or associated with solid and haematological malignancies present several functional defects in molecules involved in the triggering of effector functions (Tursz et al, 1982;Ruco et al, 1983;Frydecka, 1985;Foa et al, 1990;Nakagomi et al, 1993;Lai et al, 1996;Kono et al, 1996); these abnormalities may be secondary to the presence of the tumour (Whiteside, 1999) and are usually reversible after activation of these effectors Renner et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There are as yet only a few reports on the distribution of Tcell signalling molecules in human cancer. Decreased levels have been reported in tumour-infiltrating lymphocytes (TIL) and/or PBT cells from patients with renal cell carcinoma (CD3z) (Finke et al, 1993), colorectal carcinoma (CD3z, p56 lck ) (Nakagomi et al, 1993), melanoma (CD3z, p56 lck ) and Hodgkin's disease (Renner et al, 1996), whereas normal levels have been reported in TIL from patients with non-Hodgkin's lymphoma (CD3z, p56 lck , p59 fyn , ZAP-70) (Wang et al, 1995). Unlike solid tumours, MM is a disease where malignant cells at different stages of maturation and large amounts of tumour-derived idiotype circulate in the peripheral blood (Billadeau et al, 1992(Billadeau et al, , 1993; therefore MM PBT cells are a suitable population for investigating the effect of tumour cells on the molecular organization of the CD3/TCR complex.…”
Section: Discussionmentioning
confidence: 99%
“…Splenic T cells from tumourbearing mice are deficient in the expression of CD3z, p56 lck and p59 fyn and display abnormal protein tyrosine phosphorylation and calcium flux after activation through the TCR/CD3 complex (Mizoguchi et al, 1992;Salvadori et al, 1994). Deficiency of CD3z and p56 lck has also been reported in tumour-infiltrating lymphocytes (TIL) and peripheral blood T lymphocytes (PBT) from patients with renal cell carcinoma (Finke et al, 1993), colorectal carcinoma (Nakagomi et al, 1993), melanoma and Hodgkin's disease (Renner et al, 1996). Other reports, however, have disagreed with the view that structural alterations of the CD3/TCR signal transduction machinery represent a general phenomenon in cancer leading to tumour-specific T-cell incompetence (Wang et al, 1995;Levey & Srivastava, 1995).…”
mentioning
confidence: 98%